AI-assisted assessment and treatment of aphasia: a review - Zhong, Xiaoyun (Frontiers in Public Health, 2024)
The article "AI-Assisted Diagnosis and Treatment of Aphasia: A Review" is ideally suited for publication in "Frontiers in Public Health" for several compelling reasons. Firstly, the journal focuses on cutting-edge research that has the potential to significantly impact public health policies, practices, and understanding. The integration of AI in diagnosing and treating aphasia represents a transformative approach that aligns with the journal's mission to promote health and well-being through innovation. Secondly, "Frontiers in Public Health" emphasizes interdisciplinary research. This article bridges the gap between technology, medicine, and public health, showcasing how AI can enhance aphasia care from multiple perspectives. It highlights not only the technological advancements but also the implications for patients, healthcare providers, and public health strategies. Additionally, the journal's commitment to global health issues makes this article a perfect fit. Aphasia affects millions worldwide, and the use of AI in its management can have a global impact, offering scalable and adaptable solutions across diverse healthcare settings. Lastly, the focus on AI and its application in healthcare is timely and relevant. The article sheds light on the potential for AI to revolutionize aphasia care, offering insights that are valuable for researchers, practitioners, and policymakers alike.